Effects of Serine or Threonine in the Active Site of Typical 2-Cys Prx on Hyperoxidation Susceptibility and on Chaperone Activity - Carlos A. Tairum; Melina Cardoso Santos; Carlos Alexandre Breyer; Ana Laura Pires de Oliveira; Vitoria Isabela Montanhero Cabrera; Guilherme Toledo-Silva; Gustavo Maruyama Mori; Marcos Hikari Toyama; Luis Eduardo Soares Netto; Marcos Antonio de Oliveira (MDPI AG, 2021)
Typical 2-Cys peroxiredoxins (2-Cys Prx) are ubiquitous Cys-based peroxidases, which are stable as decamers in the reduced state, and may dissociate into dimers upon disulfide bond formation. A peroxidatic Cys (CP) takes part of a catalytic triad, together with a Thr/Ser and an Arg. Previously, we described that the presence of Ser (instead of Thr) in the active site stabilizes yeast 2-Cys Prx as decamers. Here, we compared the hyperoxidation susceptibilities of yeast 2-Cys Prx. Notably, 2-Cys Prx containing Ser (named here Ser-Prx) were more resistant to hyperoxidation than enzymes containing Thr (Thr-Prx). In silico analysis revealed that Thr-Prx are more frequent in all domains of life, while Ser-Prx are more abundant in bacteria. As yeast 2-Cys Prx, bacterial Ser-Prx are more stable as decamers than Thr-Prx. However, bacterial Ser-Prx were only slightly more resistant to hyperoxidation than Thr-Prx. Furthermore, in all cases, organic hydroperoxide inhibited more the peroxidase activities of 2-Cys Prx than hydrogen peroxide. Moreover, bacterial Ser-Prx displayed increased thermal resistance and chaperone activity, which may be related with its enhanced stability as decamers compared to Thr-Prx. Therefore, the single substitution of Thr by Ser in the catalytic triad results in profound biochemical and structural differences in 2-Cys Prx.